The Promise of Fiscal Decentralization on the Threat of Poverty Rates in Special Region - Finuliyah, Firdaus; Susilo, Susilo; Saputra, Putu Mahardika Adi (Journal of International Conference Proceedings, 2023)
This study aims to determine the effect of the fiscal decentralization component on poverty, directly or indirectly, through pro-poor expenditures in Special Regions of Yogyakarta. The Privileges of the Special Region of Yogyakarta mentioned what distinguishes it from the other provinces so that it is called a special region is the privilege to establish a social order that guarantees diversity and the critical role of the Sultanate and Duchy of Pakualaman in preserving culture. However, poverty in the Special Region of Yogyakarta is spread in every district. On the other side, more than two decades of efforts to address poverty have been through fiscal decentralization. During the era of fiscal decentralization, there were problems from the revenue and expenditure sides. It is a question related to the successful implementation of fiscal decentralization. This study uses path analysis with secondary data. The result of this study is that the component of local revenue can play a role in poverty reduction directly through local-own source revenue. The indirectly effect shows that poverty alleviation can also be done through the role of local-own source revenue through pro-poor expenditure instruments.